The Irish Parliamentary Party at Westminster, 1900-18 - Mulvagh, Conor (Book collections on Project MUSE., 2017)
The key to understanding the emergence of the independent Irish state lies in the history of Home Rule. This book offers the most comprehensive examination to date of the Irish Parliamentary Party (IPP) at Westminster during the years of John Redmond's chairmanship, 1900-18. The IPP were both the most powerful 'third party' and the most significant parliamentary challengers of the Union in the history of the United Kingdom up until the emergence of the Scottish National Party (SNP). These years saw the apparent triumph of the Home Rule cause when the Government of Ireland Act was signed into law in September 1914 but this false dawn led to the demise and electoral destruction of the IPP in 1918 when the party lost all but six seats to the political heirs of the 1916 Rising: Sinn Féin.